Prospects and challenges of yellow flesh pangasius in international markets: secondary and primary evidence from Bangladesh. Issue 9 (September 2021) - Hoque, Md. Sazedul; Haque, Mohammad Mahfujul; Nielsen, Max; Badiuzzaman,; Rahman, Md. Takibur; Hossain, Md. Ismail; Mahmud, Sultan; Mandal, Anup Kumar; Frederiksen, Marco; Larsen, Erling P.
Abstract: The projected increase in aquaculture production by 2030 will mostly occur in countries of Asia and Africa, including Bangladesh. The pangasius ( Pangasianodon hypophthalmus ) produced in Bangladesh, the second-largest producer globally, is mainly consumed by low-income domestic consumers and is poorly demanded in international markets. One reason for this is the yellow flesh of fish; consumers generally in mainstream international markets prefer to fish with white flesh. Reviewing secondary evidence and analyzing primary data, this article assesses the underlying reasons for the discolored pangasius flesh in Bangladesh and synthesizes strategies for avoiding discoloration to induce exports. The findings indicate that farming practices with high stocking density, infrequent water exchange, high organic matter in pond water, and the growth of carotenoid-containing cyanobacteria contribute to the discoloration of pangasius flesh. Artificial and natural pigments in feed and poor post-harvest handling of fish are also contributing factors. Furthermore, a positive correlation between water exchange, price, and yield at the farm is found, which indicates that farm-gate price and yield per hectare can increase with more frequent water exchange. The findings of this study provide strong evidence that improved aquaculture practices can solve the problem of discolored pangasius flesh and establish an export-oriented pangasius industry in Bangladesh. Abstract : Pangasius, Yellow fillet, Water quality, Feed ingredients, White fillet, Export.